The impact of drought stress on morpho-physiological characteristics of rapeseed cultivars (Brassica napus L.) - Saeid Zamani; Ali Arminian; Batool Zarei; Somayeh Hajinia (Oil Crop Science)
The morpho-physiological responses of 15 rapeseed genotypes to drought stress were assessed, revealing strong correlations among various characteristics. Under control conditions, the genotype Angelico fascinated the highest chlorophyll content, while Nilofar had the highest carotenoid content, grain yield, and harvest index (HI). Talaye recorded the highest proline content. Under drought conditions, Nafis maintained the highest plant height, pod number, biomass, and grain yield. Angelico demonstrated the highest chlorophyll and relative water content (RWC). Nima showed the highest carotenoid content, Zarfam excelled in chlorophyll b, and Nafis recorded the highest proline content. Overall, drought stress resulted in a significant reduction in most morpho-physiological traits. In the principal component analysis (PCA), the first two components explained a substantial portion of the variation in both control and drought conditions, facilitating the classification of the genotypes into two distinct groups. Additionally, twelve drought stress indices further categorized the genotypes, with the first two components accounting for the majority of the variation (99.45%). Notably, the Nilofar, Nima, Nafis, and Shirali cultivars were grouped together under both control and drought conditions, exhibiting the highest grain yield. These genotypes could be considered drought-tolerant varieties of this study. The research identified stable and high-performing rapeseed genotypes, which are recommended for future breeding programs.